2007
DOI: 10.1158/0008-5472.can-06-4424
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma Tumor Suppressor Status Is a Critical Determinant of Therapeutic Response in Prostate Cancer Cells

Abstract: The retinoblastoma tumor suppressor protein (RB), a critical mediator of cell cycle progression, is functionally inactivated in the majority of human cancers, including prostatic adenocarcinoma. The importance of RB tumor suppressor function in this disease is evident because 25% to 50% of prostatic adenocarcinomas harbor aberrations in RB pathway. However, no previous studies challenged the consequence of RB inactivation on tumor cell proliferation or therapeutic response. Here, we show that RB depletion faci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 40 publications
6
86
1
1
Order By: Relevance
“…Rb is frequently lost or inactivated in human cancers, for example, 25-50% of prostatic adenocarcinomas have a defective Rb pathway (Jarrard et al, 2002). Rb-depleted prostate cells fail to be growth arrested upon androgen deprivation (Sharma et al, 2007), and survivin deregulation could be one of the major contributing factors based on our current study. Moreover, we show that mutations of both CDE and CHR elements in the survivin promoter actually invert the effect of TGF-b to the one that enhanced this promoter activity, suggesting that defects in such regulation may promote the elevation of survivin by TGF-b and contribute to the oncogenic behavior of TGF-b during tumor progression.…”
Section: Discussionmentioning
confidence: 53%
“…Rb is frequently lost or inactivated in human cancers, for example, 25-50% of prostatic adenocarcinomas have a defective Rb pathway (Jarrard et al, 2002). Rb-depleted prostate cells fail to be growth arrested upon androgen deprivation (Sharma et al, 2007), and survivin deregulation could be one of the major contributing factors based on our current study. Moreover, we show that mutations of both CDE and CHR elements in the survivin promoter actually invert the effect of TGF-b to the one that enhanced this promoter activity, suggesting that defects in such regulation may promote the elevation of survivin by TGF-b and contribute to the oncogenic behavior of TGF-b during tumor progression.…”
Section: Discussionmentioning
confidence: 53%
“…These results suggest that disruption of PTTG1 may be one of the major factors contributing to androgen deprivation therapy resistance, and inhibtition of this gene may be a potential therapeutic target in the suppression of prostate cancer progression. We hypothesize that PTTG1 overexpression may be associated with advanced disease that responds poorly to hormone therapy, just as Rb loss was (Sharma et al, 2007). Further studies are necessary to clarify the role of PTTG1 in development and progression of prostate cancer.…”
Section: 3083 Pituitary Tumor Transforming Gene 1 Is An Independent mentioning
confidence: 95%
“…[111][112][113] Although a pro-apoptotic function has been reported, 114,115 many studies have found loss of RB function to enhance apoptosis due to inappropriate S-phase control, [116][117][118] causing increased sensitivity to taxanes as well as platinum compounds in different cell lines. 119,120 In contrast, p53-induced apoptosis in response to doxorubicin and combined treatment with metotrexat and 5-fluorouracil has been found to be blunted following RB knockdown in different cell lines. 121 Interestingly, Schmitt et al 41 reported the p53 and the p16/RB pathway to act in concert, inducing senescence and leading to tumour regression in response to cyclophosphamide treatment in a murine model.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%